PENINGKATAN KEMAMPUAN MENYUSUN RPP MENGGUNAKAN MODEL EXPERIENTIAL LEARNING PADA PELATIHAN MANAJEMEN MADRASAH DINIYAH DI BDK SEMARANG - Aminah, Siti (Wawasan: Jurnal Kediklatan Balai Diklat Keagamaan Jakarta, 2024)
Abstract This study aims to determine the increase of Madrasah Diniyah teacher ability to make lesson plans through the application of Experiential Learning in Madrasah Diniyah Learning Management training at the Tegal Regency Ministry of Religion Office organized by the Semarang Religious Education and Training Center in 2023. The study used an evaluative method using the Kirkpatrick model in learning level. The data analyzed were the RPP scores ​​made by participants in the Concrete Experience step and the RPP score from the Active Experimentation step. The data were processed using descriptive statistics and interpretations. The study concluded that there was a very high increase in the ability to make lessons in training participants after participating in Experiential Learning model activities. Abstrak Penelitian ini bertujuan untuk mengetahui peningkatan kemampuan menyusun RPP pada guru Madrasah Diniyah melalui penerapan Experiential Learning dalam pelatihan Manajemen Pembelajaran Madrasah Diniyah pada Kantor Kementerian Agama Kabupaten Tegal yang diselenggarakan oleh Balai Diklat Keagamaan Semarang Tahun 2023. Penelitian menggunakan metode penelitian evaluasi model Kirkpatrick level learning. Data yang dianalisis adalah nilai RPP yang dibuat peserta pada langkah Concrete Experience dan RPP hasil Active Experimentation.  Data diolah menggunakan statistic deskriptif persentasi dan interpretasi. Penelitian menyimpulkan bahwa terjadi peningkatan kemampuan menyusun RPP yang sangat tinggi pada peserta pelatihan setelah mengikuti Pembelajaran menggunakan model Experiential Learning.